An Assessment of Antimicrobial Prescription Pattern among Surgical Patients: A Hospital Based Cross Sectional Descriptive Study - Rayamajhi, Bikash Bahadur; Basukala, Sunil; Khadka, Anjan; Thapa, Narayan; Ayer, Dhirendra Bahadur (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Antimicrobials are used before, during and after surgery to prevent infections to decrease the duration of hospital stay, increase surgical outcomes and reduce health-related costs. There is inadequate evidence to determine the effective group of antimicrobials to be used in surgical prophylaxis in our settings. Methods: A hospital-based cross-sectional descriptive study involving antimicrobial prescriptions pattern among 223 surgical patients was undertaken. Information on patient’s demographic variables, diagnosis, type of surgery and wound, perioperative antimicrobial use, postoperative complications and number of antimicrobials prescribed from the essential medicine list were recorded. The antibiotic prescription patterns were assessed based on a comparison with international and national guidelines. Results: Among 223 patients, males were predominant with an overall mean age of 42.77 years. The total number of diagnoses was 30, the commonest being appendicitis (21.52%), urinary stone disease (15.69%), hernia (13.90%) and cholelithiasis (11.65%). The common surgeries performed were emergency appendectomy, hernioplasty and laparoscopic cholecystectomy. Eighteen types of drugs from seven different antimicrobial groups were used perioperatively, out of which 73% and 83% were prescribed based on international and national guidelines respectively. Conclusion: The most common antimicrobial used was third-generation cephalosporin. The postoperative antimicrobial rate was found higher compared to preoperative and intraoperative prescriptions and for a longer duration compared to national and international guidelines.